Present Situation Analysis and Medium-Term Projections for the Role of African Gas Projects in the Process of Diversification of the Gas Supply to the European Market - LAPSHINA Olga Alexandrovna (Ученые записки Института Африки Российской академии наук)
The current global gas markets agenda inspires the interest to the process of diversification of the gas supply chains in order to maintain the energy security of the regions. The article includes the author’s own analysis of the perspectives for obtaining additional volumes of gas supplies from alternative sources, based on Russian and international news sources, thematic reports and publications of research institutes such as African Energy Chamber, the Oxford Institute for Energy Studies, and statistical data. The main conclusion from the provided analysis is that, at current situation, expectations of substantial increase in gas supplies from African region in short and middle term are overstated.